THE ROLE OF COASTAL AND SMALL ISLANDS ZONATION PLAN FOR MANAGEMENT OF MARINE PROTECTED AREA: THE INDONESIAN CASE - Budy Wiryawan; Amiruddin Taher; Nina Dwisasanti (Research Center for Fisheries, 2010)
The expansion of coastal and small islands resources utilization and the increasing need to meet international and national commitments to biodiversity conservation have led to an enhanced interest in zonation plan as a tool for integrated coastal management.